Sintesis Nanokomposit -Fe2O3/SiO2 dengan Metode Salt-Assisted Spray Pyrolysis untuk Menurunkan Viskositas Minyak Berat - Anrokhi, Mohamad Samsul; Nuryadin, Bebeh Wahid; Abdullah, Mikrajuddin; Khairurrijal, Khairurrijal; Iskandar, Ferry (Jurnal Matematika dan Sains, 2017)
A α-Fe2O3/SiO2 nanocomposite as aquathermolisys catalyst material at heavy oil has been synthesized and optimized by using  Salt-Assisted Spray Pyrolysis method. The α-Fe2O3/SiO2 nanocomposite is obtained by thermal decomposition from the precursor.  The precursor is made of FeCl3, SiO2 and NaCl and water as a solvent. Concentration of FeCl3, SiO2, and NaCl are 1:1:5 in order. the composition of SiO2 in the composite is 0%, 25% and 50% of total mass, respectively. the droplets were transported to the furnace reactor using air as a carrier gas with a fixed flow rate at 5 liter/min and the furnace’s temperature is 800 °C in order to get the pyrolysis reaction. The resulted powder is then characterized by using XRD, SEM and Chatalytic aquathermolysis test. The result of XRD characterization shows that crystal peaks of α-Fe2O3 has been formed. SEM result shows nanocomposite morphology of α-Fe2O3/SiO2 with circle particle form with average particle diametre of α-Fe2O3, SiO2 25% and SiO2 50% of total mass are 765 nm, 850 nm, and 746 nm, respectively. Catalytic Aquathermolysis test showed catalyst α-Fe2O3/SiO2 50%  has catalytic properties better than catalytic properties of α-Fe2O3/SiO2 and α-Fe2O3/SiO2 25%.